Techonsortia innovation hub enhancing the R&D capability of Manila's University Belt through academe-industry-government collaboration - Abario, Jarelle Gabriel F. (College of Architecture, University of the Philippines Diliman, 2020)
As the country's capital, many consider Manila City for various academic and employment opportunities. According to Dr. Victor Fung from the book, "Univer-Cities : Strategic Implications of Asia" by Anthony Teo, "anyone who is involved in either industry or education will know that today, the relationship between the university and its city is symbiotic and dynamic." With the existence of three University Cluster Zones with a total of 75 universities/colleges, it is vital to prioritize the academic sector in the city's development plan and encourage building relationships between the universities and the city. A facility that will cater for learning, organizing, and creating for students, researchers, and other professionals is the project's vision. With the theme : "Urban Agenda", Manila's University District I was the chosen locale for the project's main agenda ; being the largest and most prominent in the country. Through in-depth research about the locale's existing condition, and the technical considerations and requirements for the project, the TECHONSORTIA Innovation Hub was proposed. The Learning Commons is one of the main facilities in the proposed project; to further encourage learning beyond formal academic grounds and to address the rising trend of collaborative working or "co-working" spaces withing the locale. The Prototyping Center and R&D Laboratories are support facilities for the Incubator where incubatees, with the guidances of their assigned mentors, may create advanced prototypes and conduct laboratory procedures, respectively. The Multi-purpose Hall was designed for events such as annual expositions, conventions, or indoor sports/activities.